Analysis of the Influence of Price Earning Ratio, Price to Book Value, Earning Per Share, Debt to Equity Ratio and Return on Equity on Share Prices in Lq45 Companies on the Indonesia Stock Exchange 2016-2020 - Novilia Tawang Wulansari; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This research aims to analyze the influence of price earnings ratio, price to book value, earnings per share, debt to equity ratio and return on equity to price share on company LQ45 in Exchange Effect Indonesia year 2016–2020. Population in study this is company Index LQ45 Which listed on the Indonesian Stock Exchange (BEI), sampling was carried out randomly purposive sampling which met the criteria and which could be analyzed was 31 company from 45 company Index LQ45. Model regression linear multiple used to analyze this research, the data in this research was analyzed using the SPSS version 25 software program. The results of this research show that price earnings ratio influential positive And significant to price share, price to book value own influence positive And significant to price shares, earnings per share have a positive and significant influence on prices share , debt to equity ratio own influence negative And No significant to price share , And returns on equity own influence negative And significant to price share